COVID-19, lockdown, elderly. Experiences of the follow up research among active older adults 2020-2021. - Patyán, László; Bene, Ágnes; Stumpf-Tamás, Ivett (Magyar Gerontológia, 2021)
Introduction, aims:The COVID-19 pandemic caused invaluable harms on the World during last two years. Among all economic and societal consequences the negative effects for elderly people was also apparent. Researches - among others - focused on the age related inequalities for accessing and using services, economic disadvantages, the decline of psychical, physical and mental conditions, reduced quality of life, increased level of loneliness, stress and depression, such as the increase and new faces of ageism.This research focused on the individual and organizational consequences of COVID – 19 pandemic and the effects of the state interventions followed by. The target group were identified as active seniors who have leading positions in different local and regional senior’s associations. These people were affected individually as a member of the age group and as an experts with organizational responsibilities as well.Research method:We chose a qualitative follow up (longitudinal) research method that was committed by semi structured phone interviews, recorded and anonymised. The time of the two data record focused and followed the main Hungarian waves of the pandemic: May – June in 2020 and June – July in 2021. Sample were collected from all districts of Hungary (n=42).Main research topics were:- The situation of the older adults (experiences about the local older people, daily life, problems, issues, social connections)- The life in the organization (activities, new initiatives, problems, issues)- Individual experiences (fears, daily life, social connections, shopping habits, use of ICT, vaccination).Results:We found significant differences on the personal life situation and the perception of pandemic and related interventions during the two waves. Pandemic situation may influenced these results. The age related “stay at home campaign” made more difficulties for the older people during the first wave, meanwhile related interventions weren’t so strict during the second wave by introducing shopping timeline for older people and night curfew for all in the late nights. Even first wave did not cause such harm like the second one in Hungary.During the first wave we found older people as a rule following citizens. They followed all the restrictions and regulations strictly. Life situations mainly were determined by the living conditions, that is means the ones who lived in the countryside mainly a house with garden experienced less negative effects than those, who lived in the housing estate area (first wave mainly fall on March – May).Older people reported increased importance of the local authorities. With the lack of central supporting interventions, local authorities played main role for local support, care and security. If the local government took care of older people they felt safety. Less interventions and coordination made older people insecured.The second wave made new situations for people. Older adults became one of the first target groups in vaccination and people started to cope with the pandemic.Older adults became more critical with governmental interventions.Critics focussed on the- pandemic related communication, the vaccination (older people mainly got Shinofarm vaccine that was not accepted in the EU at that time),- difficulties with the availability of health services, and- they experienced increased economic problems.The life in the organization: during the first wave we found frozen life of the seniors organization, cancelled and delayed programmes. Some initiatives were also reported. People preferred to keep contact via phone instead of using another ICT tools. Some of the answerer worried about the community life, how they can restart after the pandemic, others preferred the forthcoming chance for personal meetings.Seniors organisations may play an important role of the senior’s life by organizing free time and social activities, advocacy, and many other aspects of active ageing. As we made a first extract of this research further analyse will focus more on the good examples and new initiatives on the social, community and organizational levels.